Factors determining the supply of micro insurance in the South African insurance market - Chikumbu, Dudzai Christopher (University of the Witwatersrand, Johannesburg, 2024)
Access to financial services by low-income households is an important tool for meeting the millennium development goals and development. Micro insurance is a crucial financial service designed to provide affordable and accessible insurance solutions to low-income populations often excluded from traditional insurance markets. However, there is a dearth in literature especially in the South African context, looking at micro insurance from a supply-side perspective. This study sought to explore the factors determining the supply of micro insurance in the South African insurance market. Through the use of a purposive sampling method, 25 business development and market executives from selected insurance service providers participated in the study. Semi-structured interviews were used to gather data and the inductive thematic analysis was used to analyse data. Seven main themes emerged from the data. The study found that among other factors, the decision to supply or not to supply microinsurance in South Africa is mainly influenced by a combination of factors such as the distribution channels, pricing considerations, transaction costs, availability of historical data, and the regulatory framework. The study suggests strategies that leverage market insights, foster innovation, and advocate for supportive policies to expand access to affordable and sustainable microinsurance solutions for low-income populations. This would help in increasing the demand for, and supply of microinsurance in South Africa. The study concluded that while microinsurance holds promise as a tool for promoting financial inclusion in South Africa, its success depends on addressing regulatory framework challenges, the design of the products, balancing affordability and profitability, awareness issues and sustainability challenges. Through the application of a critical perspective and engaging stakeholders across sectors, policymakers, and civil society organisations, insurers can work together to unlock the full potential of microinsurance in improving the lives of low-income communities
A research report submitted in partial fulfillment of the requirements for the degree of Master of Commerce to the Faculty of Commerce, Law, and Management, School of Business Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: Micro Insurance; Supply; Low-income; South Africa; SDG-8: Decent work and economic growth